Sugarcane vinasse CO2 gasification and release of ash-forming matters in CO2 and N2 atmospheres. (October 2016) - Dirbeba, Meheretu Jaleta; Brink, Anders; DeMartini, Nikolai; Lindberg, Daniel; Hupa, Mikko
Highlights: Pyrolysis is the main mechanism for the release of organics from vinasse. About 70% of the vinasse char weight is ash. Alkali and alkali chloride release is significant above 700 °C. Char conversion is independent of CO2 concentration above 20% CO2 . Abstract: Gasification of sugarcane vinasse in CO2 and the release of ash-forming matters in CO2 and N2 atmospheres were investigated using a differential scanning calorimetry and thermogravimetric analyzer (DSC-TGA) at temperatures between 600 and 800 °C. The results showed that pyrolysis is the main mechanism for the release of the organics from vinasse. Release of ash-forming matters in the vinasse is the main cause for vinasse char weight losses in the TGA above 700 °C. The losses are higher in N2 than in CO2, and increase considerably with temperature. CO2 gasification also consumes the carbon in the vinasse chars while suppressing alkali release. Alkali release was also significant due to volatilization of KCl and reduction of alkali sulfate and carbonate by carbon. The DSC measured thermal events during heating up in N2 atmosphere that correspond to predicted melting temperatures of alkali salts in the char.